Mises en représentation de l’itinéraire culturel européen sur Facebook : entre banalité et géopolitique - Cécile Tardy; Marie Gaillard (Netcom)
This article deals with the Via Francigena, a European Cultural Route going from Canterbury to Rome along some 2.000 km, and its public representation on Facebook. Here, this communication device is not apprehended as a tool allowing only to make knowledge on Cultural Routes of the Council of Europe circulate, but as an editorial mediation which requests an act of documentary transcription as well as which conditions the ways of representing such transborder and linear spaces. We try to define the precartografic activity being constructed in the transition from the experience of the Route to the media sphere.